S, Salsa Dilla Eka Pengaruh Model CTL (Contextual Teaching and Learning) Berbantuan Video Pembelajaran Terhadap Sikap Pedulu Lingkungan dan Hasil Belajar Siswa Materi Keanekaragaman Hayati di Kalimantan: Pengaruh Model CTL (Contextual Teaching and Learning) Berbantuan Video Pembelajaran Terhadap Sikap Peduli Lingkungan dan Hasil Belajar Siswa Materi Keanekaragaman Hayati di Kalimantan Kelas VII SMPN 22 Samarinda - Dilla, Salsa; Maasawet, Elsje Theodora; Jailani; Nasution, Ruqoyyah (UNIB Press, 2025)
This study aimed to determine the effect of the CTL (Contextual Teaching and Learning) model assisted by learning videos on environmental awareness and student learning outcomes in biodiversity material in Kalimantan class VII SMPN 22 Samarinda. This study was designed to evaluate how independent factors (X) affect dependent factors (Y). This study used a pretest-posttest control group research design and quantitative quasi-experimental methodology. In environmental awareness attitudes, a t-test was obtained with a significance value of 0.003 <0.005 and the N-gain test results were 0.66 in the moderate category. In learning outcomes, a t-test was obtained with a significance value of 0.001 <0.05 and the N-Gain test results were 0.68 in the moderate category. Thus, it is known that Ha is accepted and H0 is rejected or the use of the CTL model assisted by learning videos has a significant effect on environmental awareness and learning outcomes in biodiversity material in Kalimantan class VII SMPN 22 Samarinda.